2021
DOI: 10.4103/jcar.jcar_8_21
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of correlation between clinical staging, functional staging, and histopathological grading of oral submucous fibrosis

Abstract: BACKGROUND: Oral submucous fibrosis (OSMF) is a premalignant condition with a greater prevalence in countries such as India. Various classifications have been put forth by multiple authors to determine the clinical, functional, and histopathological grade of the disease. The classification systems have greatly helped to determine the treatment modality for the patients. Understanding the correlation between the various classifications will help us determine the course of the disease, management, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“… 6 , 7 However, previous studies have found no significant correlation between clinical and histopathological grading explaining the discordance regarding vascularity. 21 , 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 However, previous studies have found no significant correlation between clinical and histopathological grading explaining the discordance regarding vascularity. 21 , 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Other features, such as hyperplasia, hyperkeratosis, and even atypia, may also be seen in the epithelium. The underlying connective tissue may occasionally show chronic inflammatory cell infiltration [16] (Figure 1f).…”
Section: Oral Submucous Fibrosis (Osf)mentioning
confidence: 99%
“…The prevalence of autoimmune diseases is higher among women of childbearing age and the recurrence of these diseases is seen during pregnancy and after childbirth. In fact, women have enhanced immune reactivity, larger antigen-presenting capability, mitogenic responses, increased antibody production, higher immunoglobulin levels, and the ability to reject allografts more rapidly 9 93. The immune system and the neuroendocrine system have many connections.…”
Section: Common Side Effects Of Hyperprolactinemiamentioning
confidence: 99%